2015
DOI: 10.1016/j.yasu.2015.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Is There a Relationship Between Patient Satisfaction and Favorable Surgical Outcomes?

Abstract: Summary Satisfaction of patients with their health care is gaining importance as a measure of hospital quality due to public reporting of these values and an increasing connection between hospital reimbursement and scores on the current tool to measure satisfaction, the Hospital Consumer Assessment of Healthcare Providers and Systems (HCAHPS) survey. We found that high hospital and surgical volume and low rates of risk-adjusted mortality are associated with high patient satisfaction. However, other favorable p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(46 citation statements)
references
References 28 publications
2
44
0
Order By: Relevance
“…This finding is supported by the significantly higher patient satisfaction in hospitals excluded from the study, which received less than 75 patient satisfaction surveys and therefore tend to be smaller hospitals. However, Tevis et al . explored the relationship between patient satisfaction and favourable surgical outcomes and noted that patients in larger hospitals were more satisfied.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is supported by the significantly higher patient satisfaction in hospitals excluded from the study, which received less than 75 patient satisfaction surveys and therefore tend to be smaller hospitals. However, Tevis et al . explored the relationship between patient satisfaction and favourable surgical outcomes and noted that patients in larger hospitals were more satisfied.…”
Section: Discussionmentioning
confidence: 99%
“…Patients' satisfaction at the time point out of PACU and 24 h after the operation was signi cantly improved after intravesical dexmedetomidine instillation because there were reductions in CRBD and catheter-induced urethral pain and patient satisfaction is closely related to the postoperative outcomes [37]. The improvement in the patients' satisfaction might reduce their CRBD and urethral pain.…”
Section: Discussionmentioning
confidence: 98%
“…Although patient experience is categorically linked to CMS reimbursement via HCAHPS, there is no clear relationship between patient satisfaction/experience and clinical outcomes. Though some studies have shown a correlation between HCAHPS [4] or alternate patient satisfaction surveys [5,6] and clinical outcomes, a growing body of data demonstrates the absence of such a correlation [7], particularly in surgical specialties [8][9][10][11][12]. In fact, one study reported that increased mortality and complication rates were associated with higher patient satisfaction scores [13].…”
Section: Patient Experience and Reimbursementmentioning
confidence: 99%